1987
DOI: 10.1164/ajrccm/136.1.174
|View full text |Cite
|
Sign up to set email alerts
|

“Pigtail” Catheter Drainage in Thoracic Surgery

Abstract: Small-bore percutaneous drainage catheters have been used extensively in the management of abdominal disorders and are gaining acceptance in thoracic problems. The records have been reviewed in 44 consecutive patients in whom 53 small-bore catheters were placed for thoracic disease, including empyema, 20; effusion, 9; pneumothorax, 10; lung abscess, 4; and mediastinal cyst, 1. Insertion was performed under fluoroscopy in 88%, computed tomography in 6%, and ultrasonography in 6%. Catheters ranged in size from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…The success rate of drainage by chest tube as the first procedure for the management of empyema is low [21][22][23][24]. In our study, 72 patients (47 %) underwent other procedures such as second chest tube, VATS, or thoracotomy.…”
Section: Discussionmentioning
confidence: 61%
“…The success rate of drainage by chest tube as the first procedure for the management of empyema is low [21][22][23][24]. In our study, 72 patients (47 %) underwent other procedures such as second chest tube, VATS, or thoracotomy.…”
Section: Discussionmentioning
confidence: 61%
“…Multiple loculations may require multiple catheters for adequate drainage. 10 The presence of thick fibrous peel of chronic empyema is not a contraindication to initial percutaneous pigtail catheter drainage and has been used with some success after failure of stiff tube thoracostomy. 10 Image-guided approaches using CT, sonography, or fluoroscopy ensures proper catheter placement, and is successful in a high percentage of cases.…”
Section: Discussionmentioning
confidence: 99%
“…2 For drainage of pleural collections, two drainage systems are commonly utilized: chest tube drainage and pigtail catheter drainage. 3,4 Each of them has its own indications, advantages, and disadvantages. The aim of this article is to provide a review on both systems, and to compare the reported safety, efficacy, and complications of each.…”
Section: Introductionmentioning
confidence: 99%
“…It is beneficial for drainage of non-viscid non-coagulable collections such as urine, pancreatic secretions, biliary secretions, or even air. 4 Pigtail catheter drainage is performed through ultrasoundguided transcutaneous insertion of the catheter into the target fluid collection. 5 The catheter is then fixed to the skin with sutures, and the other tip is sometimes put under water seal in certain condition such as drainage of pneumothorax.…”
Section: Introductionmentioning
confidence: 99%